Possibilities of therapeutic drug monitoring during folic acid supplementation for prevention of neural tube defects - O. E. Zaytseva (Izdatelstvo OKI, 2018)
Periconceptional folic acid (FA) supplementation for prevention of neural tube defects (NTD) used around 30 years. The effect of FA using for prevention of NTD expected only in case of folate deficiency. The World Health Organization (WHO) identified biomarkers of folate status. The concentrations of serum and red blood cells folate, plasma concentration of homocysteine have potential for therapeutic drug monitoring during FA supplementation. FA should be intake only if it needed clearly in pregnancy. Pregnant women often exceed the tolerable upper intake level of FA. Maternal excessive intake of FA during pregnancy increases risks of epigenetics effects for offspring. The aim of the practical recommendations is to increase awareness among physicians about the most common causes of folate deficiency, the possibility of routine use of biomarkers of folate status, as therapeutic drug monitoring during FA supplementation for prevention of NTD, in accordance with the data of evidence based medicine and WHO guidelines (2015).